Effects of Added Soybean Isoflavones in Low Crude Protein Diets on Growth and Carcass Performance of Finishing Pigs from 260 to 320 lb - L. L. Thomas; M. D. Tokach; J. C. Woodworth; R. D. Goodband; S. S. Dritz; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 282 pigs (DNA 600 × 241, initially 259.3 lb) were used in a 26-d trial to determine the effect of added soybean isoflavones on growth performance and carcass characteristics of finishing pigs fed low crude protein (CP) diets. Pens of 7 or 8 pigs were allotted by body weight (BW) and randomly assigned to 1 of 4 dietary treatments with 9 replications per treatment. Experimental diets were arranged in a 2 × 2 factorial with main effects of CP (13% or 10%) and isoflavone (none or 0.05% of the diet). To achieve desired CP levels, soybean meal (SBM) inclusion was reduced from 13.6 to 4.1% of the diet. Pigs were weighed weekly and at d 26 transported to a packing plant for processing and carcass data collection. For overall growth performance, there was no evidence for an interaction between CP and added isoflavones. Pigs fed diets containing 13% CP had increased (P<0.005) average daily gain (ADG) and subsequently final BW and better feed efficiency (F/G) compared with pigs fed 10% CP. Carcass yield increased (P= 0.030) for pigs fed the 10% CP diet compared to pigs fed the 13% CP diet. There was no evidence that including isoflavones in the diets influenced growth performance or carcass characteristics. In summary, the reduced growth performance observed in pigs fed the 10% CP and 4.1% SBM diets does not appear to be related to soy isoflavone concentration.
Keywords: Crude protein; isoflavone; finishing pigs; soybean meal